Feeling trapped : social class and violence against women - Ptacek, James (University of California Press, 2023)
"The relationship between class and intimate violence against women is much misunderstood. While many studies of intimate violence focus on poor and working-class women, few examine the issue comparatively in terms of class privilege and class disadvantage. James Ptacek draws on in-depth interviews with sixty women from wealthy, professional, working-class, and poor communities to investigate how social class shapes both women's experiences of violence and the responses of their communities to this violence. Ptacek's framing of women's victimization as "social entrapment" links private violence to public responses and connects social inequalities to the dilemmas that women face"-- Provided by publisher.
Keywords: Intimate partner violence -- United States -- Case studies.; Social classes -- United States -- Case studies.; Women -- Violence against -- United States -- Case studies.; Violence entre partenaires -- États-Unis -- Études de cas.; Classes sociales -- États-Unis -- Études de cas.; Femmes -- Violence envers -- États-Unis -- Études de cas.; SOCIAL SCIENCE / Criminology; Intimate partner violence; Social classes; Women -- Violence against; United States; Electronic books.; Case studies; Case studies.; Études de cas.